The Impact of Industrial Disharmony on Employee Performance in Tertiary Institutions in Delta and Edo States - Gberevbie, Christopher; Okereka, Onofere Princewill; Mukoro, Akpomuvire (Universitas Muhammadiyah Ponorogo, 2025)
Although industrial harmony is essential for achieving academic excellence and maintaining a productive educational system in Nigeria, incidents of industrial disharmony in tertiary institutions have become increasingly frequent, intense, widespread, and prolonged. In light of this, the study investigated the causal relationship between industrial disharmony and employee performance in selected tertiary institutions in Delta and Edo States. Utilizing a cross-sectional research design, the study employed a structured survey instrument to collect data from a sample of 243 employees, randomly selected from Delta State University, Abraka; University of Benin, Benin City; Delta State Polytechnic, Oghara; Auchi Polytechnic, Auchi; Delta State College of Education, Warri; and the College of Education, Igueben, Edo State. The research was grounded in the industrial relations system theory, which provides an analytical framework for understanding a broad range of industrial relations practices and phenomena. Six hypotheses were tested at a 0.05 level of significance, with data analysis conducted using the Statistical Package for Social Sciences (SPSS, version 23.0, 2020). Pearson’s correlation coefficient and linear regression analysis were used to test the hypotheses. The findings revealed that poor implementation of promotion policies significantly increased grievance frequency; non-implementation of agreements significantly heightened the occurrence of strike actions; union leaders’ integrity had a significant positive impact on employee welfare; and industrial union strikes significantly contributed to poor employee performance in tertiary institutions in Delta and Edo States. The study concluded that industrial harmony positively and significantly affects employee performance in these institutions. Among the recommendations, the study emphasized the importance of sincere engagement between tertiary institutions and workers’ unions through collective bargaining. This approach would help workers better understand the challenges and constraints faced in addressing their demands. Moreover, fostering a harmonious work environment relies more on mutual understanding between unions and institutional management rather than on fully satisfying the demands of both parties, which may not always be feasible.